Malaysian internal and external auditor perceptions of the effectiveness of red flags for detecting fraud. (1st January 2013) - Moyes, Glen D.; Young, Randall; Mohamed Din, Hesri Faizal
The purpose of this study is to examine effectiveness of US Statement of Auditing Standard (SAS) No. 99 red flags in detecting fraud as perceived by both the Malaysian internal auditors and external auditors. SAS No. 99 and International Standards on Auditing require external auditors to use red flags in detecting fraudulent financial reporting activities, while conducting financial statement audits. Questionnaires were completed by 52 Malaysian internal auditors and 40 Malaysian external auditors. Statistical analysis determines that Malaysian external and internal auditors perceive each of the 59 red flags as perceiving different levels of effectiveness in detecting fraudulent financial reporting activities. In addition, significant differences were found to exist between Malaysian external auditors and Malaysian internal auditors concerning the fraud detecting effectiveness of 12 red flags.